2012
DOI: 10.1007/s11126-012-9222-6
|View full text |Cite
|
Sign up to set email alerts
|

Professionals’ Attitudes After a Seclusion Reduction Program: Anything Changed?

Abstract: Changing professionals’ attitudes toward seclusion is seen as an important condition to reduce its use. The purpose of this study was to determine whether professionals from a mental health institute in the Netherlands changed in their attitudes toward seclusion after implementation of a multifaceted seclusion reduction program. Professionals working on four acute admission wards filled in the Professional Attitudes Toward Seclusion Questionnaire (PATS-Q) before and after a seclusion reduction program. Changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…Furthermore, a study that investigated how a seclusion reduction programme could affect seclusion practices and attitudes found no difference in the use of alternative measures before and after the programme (Mann‐Poll et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, a study that investigated how a seclusion reduction programme could affect seclusion practices and attitudes found no difference in the use of alternative measures before and after the programme (Mann‐Poll et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…The most surprising evidence for the lack of alternative measures is that nursing staffs’ use of containment alternatives did not decrease after a seclusion reduction programme (Mann‐Poll et al . ). Certain nurses recognized various alternatives to containment methods (Gelkopf et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, a converging body of evidence suggests that exposure to stressors and subsequent coping responses play an important role. For instance, several theories on racial disparities in mental and physical health outcomes posit that African Americans are more likely to experience chronic perceived stress (e.g., racism, lower socio-economic position), and have fewer environmental resources available to cope with negative affect, which subsequently impacts psychiatric symptoms (Clark, Anderson, Clark, & Williams, 1999; Kim, 2013). Given differences in daily stressors and coping resources, it is plausible that low DT may manifest differently in African American and Caucasian adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, many previous studies have shown that proper training could play a vital role in changing attitudes, in general, positively . This study's concern was about nurses’ attitudes toward coercive measures.…”
Section: Introductionmentioning
confidence: 87%